Technologies of the spouse: intimate surveillance in Senegalese transnational marriages. (10th January 2014) - HANNAFORD, DINAH
Abstract Rapid advances in communication technology in the last 20 years have enabled migrants to sustain social and economic investment in multiple geographic locations, or, to be transnational. In this article, by analysing non‐migrant Senegalese women's experiences in marriages with migrant Senegalese men, I critically engage in discussions about the role of technology in transnational family dynamics. In the intimate negotiations of transnational married life, these women feel profoundly ambivalent about the role of communication technologies in their lives. Instead of enabling 'emotional closeness', the virtual presence of their absent husbands frequently represents a spectre of suspicion, control and surveillance.